2007
DOI: 10.1063/1.2671184
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative characterization of zigzag spatiotemporal chaos in a system of amplitude equations for nematic electroconvection

Abstract: It has been suggested by experimentalists that a weakly nonlinear analysis of the recently introduced equations of motion for the nematic electroconvection by M. Treiber and L. Kramer [Phys. Rev. E 58, 1973 (1998)] has the potential to reproduce the dynamics of the zigzag-type extended spatiotemporal chaos and localized solutions observed near onset in experiments [M. Dennin, D. S. Cannell, and G. Ahlers, Phys. Rev. E 57, 638 (1998); J. T. Gleeson (private communication)]. In this paper, we study a complex spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…An important question is which of the observed behaviour is found in a spatiotemporal setting, when the normal form is extended to the system of globally coupled Ginzburg Landau equations introduced in [32] and investigated to some extent in [22,33,36]. A preliminary study for fixed values of the parameters in region A of Figure 2(c) [22] showed that the Ginzburg Landau dynamics depends on the initial conditions.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…An important question is which of the observed behaviour is found in a spatiotemporal setting, when the normal form is extended to the system of globally coupled Ginzburg Landau equations introduced in [32] and investigated to some extent in [22,33,36]. A preliminary study for fixed values of the parameters in region A of Figure 2(c) [22] showed that the Ginzburg Landau dynamics depends on the initial conditions.…”
Section: Discussionmentioning
confidence: 96%
“…As is apparent from (2), z 1 and z 3 are amplitudes of waves travelling in the directions À(p c , q c ) and (p c , q c ), and z 2 and z 4 are amplitudes of waves travelling in the directions (p c , Àq c ) and À(p c , Àq c ), respectively. The two wave pairs are sometimes referred to as 'zig' and 'zag' waves [35,36]. When the spatial periodicity constraint is removed, the representation (2), with the z j considered time and space dependent, leads to a globally coupled system of PDEs of the Ginzburg Landau type, whose spatially uniform solutions are governed by (1) [32].…”
Section: The Normal Formmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the temporal dynamics resulting from Simulation 1 is a low-dimensional temporal chaos, reminiscent of the chaotic attractor of the normal form for the same values of the coefficients, but with a few additional modes being activated. We note that a similar type of low-dimensional spatiotemporal chaotic dynamics shown by (7), referred to as "zigzag-chaos", has been identified and analyzed in [44].…”
Section: Numerical Simulations Of the Gccgle: Bistability Of Low And mentioning
confidence: 61%
“…We use the method of Karhunen-Loeve (KL) spatial modes decomposition combined with time-series analysis of the resulting mode amplitudes [5] . The KL modes are orthogonal and represent statistically independent parts of the data and are ranked according to the amount of data correpsonding to them.…”
Section: Karhunen-loeve Analysismentioning
confidence: 99%